2018
DOI: 10.1186/s12886-018-0713-6
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dimensions of the Chinese adolescents with keratoconus

Abstract: BackgroundAdolescent KC is a special segment of the general KC population because an adolescents’s eyes are still susceptible to blurred vision and optical defocus during the sensitive period of ocular and visual development. In the present study, we evaluated the ocular dimensions of 53 KC adolescents.MethodsOne hundred and six KC eyes of 53 (42 boys and 11 girls) KC adolescents (age 15.5 ± 1.7 years, range 11 to 18) were involved in this retrospective study. The eye with more severe KC (Severe Group) of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…It usually appears in the second decade of life, although cases at a younger age [15][16][17][18] have been reported. Therefore, the interest of the current study in highlighting the presence of the disease since childhood and our results agree with those that study KC cases with a presentation in the pediatric age [19][20][21][22][23] . In the case of our study, they are patients who usually came to the office for different reasons: ophthalmological examination as a requisite to enroll in school, renewal of optical correction, family history of the disease, and parents request for corneal topography, among others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It usually appears in the second decade of life, although cases at a younger age [15][16][17][18] have been reported. Therefore, the interest of the current study in highlighting the presence of the disease since childhood and our results agree with those that study KC cases with a presentation in the pediatric age [19][20][21][22][23] . In the case of our study, they are patients who usually came to the office for different reasons: ophthalmological examination as a requisite to enroll in school, renewal of optical correction, family history of the disease, and parents request for corneal topography, among others.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding sex, there is no consensus in the literature regarding whether the disease is more frequent in one or the other; different series report the disease in both sexes, without statistically significant differences between them 12,19,20 . The disease is hereditary and there are families where both male and female children inherit the disease [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually visit the hospital when they are unable to obtain adequate care at optometry clinics. The rural population in Henan Province is relatively larger, and the per capita disposable income in Henan Province is lower than those in Beijing (northern China) and Shanghai (eastern China) 16 , 17 . The percentage of patients with KC in the capital district is much higher because the diagnosis is not covered by health insurance.…”
Section: Discussionmentioning
confidence: 93%
“…However, the disease was defined based on only corneal refractive power, and the corneal topography that could detect minor forms of KC was not included in the study design. Jian et al 17 evaluated the ocular dimensions of KC eyes from Shanghai, eastern China, and found that KC eyes were characterized by deeper anterior chamber depths but shorter optical axial lengths and posterior segment lengths in adolescents (11–18 years). The demographic data, VF questionnaire data and corneal biomechanics of KC patients were not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular biometric characteristics, such as AL, anterior chamber depth (ACD), white-to-white (WTW) distance, central corneal thickness (CCT), keratometric power (K), and corneal astigmatism (CA) have been described previously ( 1 7 ). However, few studies have been focused on the overall anterior and posterior segment dimensions of the eyes ( 8 , 9 ). Nowadays, modern optical biometry devices can measure different axial biometric parameters of the eyes, including ACD and AL ( 10 ).…”
Section: Introductionmentioning
confidence: 99%